Automatic System for Creating Educational Robotics Courses in the Repo-Educ System - Curvelo, Carla Da Costa Fernandes; Rossiter, Sarah Thomaz De Sá; Gonçalves, Luiz Marcos Garcia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Aiming to reduce the distance from the teachers of propaedeutic subjects to the use of educational robotics in the classroom, we propose the creation of a module in the Repo-Educ system, an automatic system for the formation of educational robotics courses. This module will be able to help teachers who wants to start working on a certain subject of the Common National Curricular Base, proposing a robotics course for the chosen subject and auxiliary subjects. Through these courses, teachers will have access to the lesson plans already registered in the system, which have a complete explanation of the robot’s assembly, programming, and use. It is hoped that the teacher will learn how to manage and use robotics in the classroom, adding value and knowledge to his or her students.